PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK DI KELAS IV SEKOLAH DASAR NEGERI (SDN) NO. 89 SIPATANA - Ningsih, Sri Wulandari; Amin, Basri; Nurainun, Nurainun (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
This study aims to develop a pop-up book as learning medium for the IPAS (Natural and Social Sciences) subject on the topic of Indonesian cultural heritage for fourth-grade students SDN No. 89 Sipatana Gorontalo City. The objective is to create a medium that meets both feasibility and practicality criteria. The research adopts the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The feasibility of the pop-up book was assessed through expert validation involving media experts, content experts, and user experts (teachers). The results indicate that the pop-up book effectively captures students’ attention during the learning process. During a limited trial, students demonstrated positive responses, as reflected in both their active engagement in learning and responses to the distributed questionnaires. Additionally, teachers reported that the medium facilitated the teaching process, particularly in delivering abstract content. However, the study also identified a limitation in the material durability of the pop-up book, which may require extra maintenance when used repeatedly.  Despite this limitation, the findings suggest that the use of pop-up books can serve as an effective instructional strategy in IPAS learning, especially for topics related to Indonesian cultural heritage. ABSTRAKStudi ini bertujuan mengembangkan media pembelajaran pop up book mata pelajaran IPAS pada materi kekayaan budaya Indonesia di kelas IV SDN No. 89 Sipatana Kota Gorontalo yang memenuhi dalam kriteria kelayakan dan kepraktisan. Dalam penelitian pengembangan media pembelajaran menggunakan model pengembangan ADDIE, yang mencakup tahap Analysis, Design, Development, Implementation, dan Evaluation. Dalam validasi kelayakan media pop up book diuji oleh ahli media, ahli materi, dan ahli pengguna (Guru). Hasil analisis menunjukkan bahwa media pembelajaran pop up book mampu menarik perhatian peserta didik dalam proses belajar mengajar. Selama uji coba terbatas, peserta didik menunjukkan respon positif melalui keterlibatan peserta didik dalam pembelajaran dan terhadap angket respon yang telah dibagikan. Selain itu, Guru menyatakan bahwa media ini mempermudah proses belajar mengajar, terutama menyampaikan materi yang berisfat abstrak. Sementara itu, terdapat keterbatasan ditemukan pada ketahanan bahan media pembelajaran pop up book, yang perlu perawatan lebih apabila digunakan secara berulang. Meskipun demikian, temuan ini menunjukkan bahwa penggunaan media pembelajaran pop up book dapat menjadi strategi dalam pembelajaran IPAS terutama dalam materi kekayaan budaya Indonesia.